Exploring mHealth app utilization for diabetes self-management: survey insights from a northern district in Malaysia - Premaa Supramaniam; Ying-Shan Beh; Suria Junus; Philip Rajan Devesahayam (BMC Public Health)
Abstract Background Mobile health applications (mHealth apps) offer potential benefits for improving diabetes management, such as better glucose monitoring and patient engagement, but their widespread adoption faces challenges, including privacy concerns and user adherence. This research investigates mHealth app usage among patients living with diabetes in Kinta District, Perak, exploring experiences, challenges and patient perceptions regarding diabetes management using mHealth apps. Methodology A cross-sectional community survey was conducted in September till November 2020 across nine government health clinics focusing on diabetes mellitus (Type 1 or Type 2) patients, aged 18 years and older, receiving Diabetes Medication Adherence Counseling (DMTAC) services and able to use smart devices. A self-developed questionnaire with four sections was used to gather demographic information, explore mHealth apps usage and understand both users and non-users’ experiences and perceptions. The questionnaire was tested through cognitive debriefing, translated into Malay, pre-tested and finalized by the expert committee. The questionnaire was digitally implemented using Google® Form and QR code. After obtaining informed consent, data collection was performed by the trained DMTAC pharmacists. Statistical analyses involved descriptive and inferential analyses. Results The study analyzed the engagement of 295 patients living with diabetes with mHealth apps. Females (54.9%), of Malay ethnicity (58.3%) and with a mean age of 53.8 years (SD: 12.38) constituted the majority. Diabetes duration had a median of 6 years (IQR: 3.0, 10.0) with prevalent comorbidities like hypertension (58.0%) and dyslipidemia (42.7%). Most patients were employed (44.7%) and their primary source of diabetes management information was through healthcare providers (92.5%). Despite the high app use for social interaction, only 13.6% used mHealth apps for disease management. Users were influenced by social media (65.0%) and favored for wellness apps and disease monitoring. Users perceived the mHealth app as useful (97.5%), yet faced challenges over the app initiation, charges and data security. Non-users cited lack of awareness (70.2%), struggled with app startup (22.4%) and preference for conventional healthcare visits (22.0%). In multivariable analysis, longer diabetes duration reduced mHealth app usage (p = 0.046), while multimorbidity increased the likelihood (p = 0.001). Awareness of the availability of health apps significantly influenced the usage of mHealth apps (p < 0.001). Conclusion The findings highlight the underutilization of mHealth apps for diabetes management despite their perceived usefulness. Challenges faced by users and non-users underscore the need for more awareness, thus encourage widespread acceptance and usage of mHealth apps in diabetes care.